Effect of temperature and water activity on growth and ochratoxin A production boundaries of two Aspergillus carbonarius isolates on a simulated grape juice medium - Tassou, C. C.; Natskoulis P. I.; Magan, Naresh; Panagou, Efstathios Z. (Blackwell Publishing Ltd, 2009)
Aims: To develop and validate a logistic regression model to predict the growth and ochratoxin A (OTA) production boundaries of two Aspergillus carbonarius isolates on a synthetic grape juice medium as a function of temperature and water activity (aw).
Keywords: Aspergillus carbonarius; fungal growth; ochratoxin A; predictive mycology; probabilistic models; wine grapes